Analisis Transformasi Birokrasi Melalui Pengembangan e-Government di Indonesia - Sumardi Sumardi; Adi Nawir; Suardi Mukhlis (Journal of Government Insight, 2021)
This paper aims to determine the Analysis of Bureaucratic Transformation through the Development of e-Government in Indonesia. The methodology used in this study uses a library research approach, and data collection is carried out by reviewing and exploring journals, books, and other supporting documents related to the research focus. The results of the study concluded that e-government must be implemented seriously and consistently so that it can support the transparency of public services. Bureaucratic transformation through e-government must be carried out with the support of several factors, namely, regulations, organizational structure, organizational culture, system reconstruction. E-government has the potential to support the transparency of public services through a consistent monitoring system, extensive knowledge of information technology and integrity.